ANALISIS TINGKAT KEPUASAN PETERNAK PLASMA TERHADAP KINERJA KEMITRAAN PT. CIOMAS ADISATWA DI KEC. SIMBANG KAB. MAROS - Bashar Nur Takbir; Astati, Andi Suarda; Muhammad Nur Hidayat (Jurnal Ilmu dan Industri Peternakan, 2015)
ABSTRACT. The research aims to determine the partnership held by PT. Ciomas Adisatwa and the level of satisfaction plasma breeders of the performance services PT. Ciomas Adisatwa. This research was conducted at PT. Ciomas Adisatwa Simbang rigency Maros of districts. The research method is field survey by using a questionnaire with 30 sampling. The results show that : 1) Pattern of partnerships by PT. Ciomas Adisatwa is core-plasma pattern, where the company as core and breeder as plasma. The advantages of this pattern is certainty means of production, services or guidance, and post-harvest services. 2) Overall assessment plasma of breeders to the PT. Ciomas Adisatwa is conform with the hope that the accumulated number levels of satisfaction on the performance of the core plasma at 48,36% (content category).